A fever of the blood - De Muriel, Oscar (Pegasus Crime, 2017)
New Year's Day,1889. In Edinburgh's lunatic asylum, a patient escapes as a nurse lays dying. Leading the manhunt are legendary local Detective 'Nine-Nails' McGray and Londoner-in-exile Inspector Ian Frey. Before the murder, the suspect was heard in whispered conversation with a fellow patient- a girl who had been mute for years. What made her suddenly break her silence? And why won't she talk again? Could the rumours about black magic be more than superstition? McGray and Frey track a devious psychopath far beyond their jurisdiction, through the worst blizzard in living memory, into the shadow of Pendle Hillhome of the Lancashire witches- where unimaginable danger awaits.